Development of a Theoretical Framework and a Measure of General Organizational Means-Efficacy. Issue 1 (1st January 2021) - Agars, Mark; Kottke, Janet L.
ABSTRACT: Means-efficacy was introduced by Eden as one's perception of available organizational resources, a form of external efficacy which, together with internal (i.e., self) efficacy comprises a larger subjective efficacy construct. We further develop means-efficacy, elucidate its place in motivational theory, and present three studies to construct and validate the General Organizational Means-Efficacy Scale (GMES), the first such measure to date. Results support a general means-efficacy construct and provide convincing psychometric support for the GMES. We argue motivation theory will be advanced by adopting a general form of means-efficacy, and that the GMES provides a useful tool for future validation and other studies.